2010
DOI: 10.1007/s13206-010-4112-1
|View full text |Cite
|
Sign up to set email alerts
|

A relationship between miRNA and gene expression in the mouse Sertoli cell line after exposure to bisphenol A

Abstract: Presently, it is important to address the harmful effects of environmental chemicals on living organisms. The toxic effects of bisphenol A (BPA), one of the endocrine disruption chemicals (EDCs), have been documented in many studies since the 1930s. However, BPA has continued to be used to make polycarbonate plastic, etc. Therefore, it is necessary to conduct toxicogenomic studies to assess the harmful effects of BPA. In this study, microarray technology was used to study the harmful effects format the genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…The effect of BPA exposure on the mammalian miRNome has been investigated in few studies. BPA has been shown to alter the expression profiles of miRNA in human placenta cells [ 129 ] and MCF-7 breast cancer cells [ 130 ], as well as in sheep ovaries [ 131 ] and murine testicular TM4 cell line [ 132 ]. To our knowledge, the effect of BPA on miRNA omics has not been investigated in zebrafish yet.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of BPA exposure on the mammalian miRNome has been investigated in few studies. BPA has been shown to alter the expression profiles of miRNA in human placenta cells [ 129 ] and MCF-7 breast cancer cells [ 130 ], as well as in sheep ovaries [ 131 ] and murine testicular TM4 cell line [ 132 ]. To our knowledge, the effect of BPA on miRNA omics has not been investigated in zebrafish yet.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in both slower proliferation rate and higher sensitivity to the DNA damaging agent bleomycin [ 27 ]. Beside, mouse sertoli cell line TM4 exposed to BPA for 24 h was reported to have two-fold up or down-regulated 37 miRNAs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al (2015) reported significantly upregulated mRNA expression of a major androgen binding protein Scgb2a1 that was linked to altered acetylation of H3K9 in the rat prostate [58]. Disruption of ncRNA expression has also been reported upon BPA exposure in human placental cells and mouse Sertoli cells [59,60]. Although these observations demonstrate strong evidence for perinatal BPA exposure altering epigenetic regulation, whether these epigenetic changes are mediated by ligand-activated transcription factors and/or directly drive the observed physiological changes remains to be determined.…”
Section: Bpa Phthalates and Parabens: Modes And Mechanisms Of Acmentioning
confidence: 99%